Stock market liberalization: implications on cost of capital in emerging Islamic countries. Issue 2 (11th November 2019) - İlhan, Bilal
Abstract : Purpose: Most of the major Islamic countries' stock exchanges have not been able to perform at the same pace with the major emerging countries' stock exchanges since the mid of 1990s. The purpose of this paper is to examine the implications of stock market liberalization on cost of capital as one of the crucial driver to stock market development and physical investment growth in emerging Islamic countries. Design/methodology/approach: This study employs static panel data techniques on the sample of seven emerging Islamic countries over the years 1989-2008. Findings: The findings of this study suggest that stock market liberalization significantly reduces cost of capital in the stock markets of sample Islamic countries, which carries policy-oriented implications. Reduction in the cost of capital increases the number of exchange-traded companies, profitability of projects and aggregate investment level; therefore, the study findings are highly concerned by the economic policymakers, corporations and investors alike. Research limitations/implications: In the literature, different proxies are employed to measure stock market liberalization and cost of capital as well. Due to data limitations, this study could not employ different proxies for both, especially for stock market liberalization, for robustness purpose. That limitation further restricted the coverage of Islamic stock markets and time period. Therefore, generalization of the study results for overall Islamic stock markets can be slightly drawn. Originality/value: The paper provides further understanding regarding the effects of SML on cost of capital, thereby indirectly on the stock market development, in the context of EIC.